2020
DOI: 10.1097/mrr.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dependence of muscle strength measurements and the risk of falls in the elderly

Abstract: Low muscle strength appears to increase balance disorders and the tendency to fall. Diagnostic terms indicate that sarcopenia and risks of falling are related. The aim of this study is to verify which diagnostic tools used for the assessment of muscle strength in sarcopenia can be used for fall risk assessment in older women. The study included 56 females [71.77 ± 7.43(SD)]. The results of handgrip strength (HGS) and knee extensors torque [knee extension strength (KES)] were compared to the results of stabilog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Postural control is a term used to describe the way in which the central nervous system (CNS) regulates information from other systems to produce appropriate motor output to maintain an upright and controlled posture. It has been demonstrated [2][3][4] that ageing impairs the capability of the CNS to process these signals and reduces the capacity to modify adaptative reflexes. Additionally, damage to any of these balance regulation levels influences the output of the postural system, resulting in an increased risk of postural instability, falls and consequently fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Postural control is a term used to describe the way in which the central nervous system (CNS) regulates information from other systems to produce appropriate motor output to maintain an upright and controlled posture. It has been demonstrated [2][3][4] that ageing impairs the capability of the CNS to process these signals and reduces the capacity to modify adaptative reflexes. Additionally, damage to any of these balance regulation levels influences the output of the postural system, resulting in an increased risk of postural instability, falls and consequently fractures.…”
Section: Introductionmentioning
confidence: 99%
“… Lu et al (2020) showed that HG strength correlates with arm and leg strength and represents whole-body muscle strength. KES is a method for assessing lower limb strength and predicting falling risk ( Bobowik and Wiszomirska, 2020 ). Consistent with Hsu et al (2019) , our study showed that RT significantly improved both HG and KES, and MT improved GS.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the risk factors associated with falls were based primarily on elderly patient cohorts and not on amputees. Other studies also include other factors such as age-related, intellectual disability, lower limb strength, and cerebrovascular disease that are related to falling risk [25][26][27]. Our cohort population for TFA is younger than previously studied with an age range of 20 to 45 years old.…”
Section: Discussionmentioning
confidence: 99%